The Mosque as a Socio-Religious Space for the Economic Empowerment of the Muslim Community: A Case Study of the Nurul Jannah Mosque at Petrokimia Gresik - Moch. Herma Musyanto; Muhammad Rijal Nasrulloh; Abdul Wadud; Ahmad Mushthafa Musyanto; Abd. Halim (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
In the context of contemporary Muslim society, mosques can no longer be understood merely as places of worship, but also as socio-religious institutions with the potential to play a role in local economic development. This article aims to analyze the role of the Nurul Jannah Petrokimia Gresik Mosque as an actor in local economic development and to explain the contribution of mosque-based economic programs to strengthening the livelihoods of the surrounding community. This study employs a qualitative approach using a case study design. Data were collected through in-depth interviews with mosque administrators and supported MSME operators, observations, and documentation, and were analyzed using the Miles and Huberman interactive model through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Nurul Jannah Mosque plays an active role in transforming informal economic activities into a more structured business ecosystem through the provision of business spaces, the mobilization of institutional resources, facility support, promotion, and relatively organized program management. This program is built on a hybrid resource configuration—a combination of corporate assets, community contributions, and institutional management by the mosque. Research findings also indicate that the program’s contribution to community livelihoods is tangible, though not uniform. For some business owners, this program expands market access, increases revenue, and supports business expansion; however, for others, the primary benefits are more evident in the stability of business operations, legal compliance, convenience, and the sustainability of economic activities. This article emphasizes that mosques can function as intermediary institutions that connect religious values, local resources, and community economic needs within a framework of community development that is more organized, adaptive, and sustainable